Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use